Makna Sampul Majalah Tempo tentang Pemilihan Umum edisi Januari 2024 - Syafitri, Dwi Imas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Tempo magazine covers use strong visuals and striking illustrations to highlight the main topics of each issue. This research analyzes the visual meaning of three covers of the January 2024 edition of Tempo magazine—"Angan-anganan Satu Lapir," "Omon-omon Bansos," and "Operator President Jokowi"—using Charles Sanders Pierce's semiotic theory and visual analysis. This study examines elements such as illustrations, typography, colors and symbols on the cover to reveal the messages and themes conveyed. Qualitative methods are used to explore the message the magazine wants to convey. The research results show that cover design with the right use of color, typography, layout, visual identity, illustrations and infographics plays an important role in shaping readers' perceptions. Colors such as dark red and white reflect political pressure and honesty, while light blue creates a sense of stability. These symbols are effective in conveying the political dynamics of the 2024 Presidential Election in Indonesia and the impact of loyalty to President Jokowi on the election process and support for his son's candidacy.